Income under-reporting and tax evasion - Hai Anh La; Duc Anh Dang (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2018)
Personal income tax is attracting more attention from the Vietnamese government, which has been looking for a way to reinforce its budget revenue. Although this tax plays an increasing role, representing 7.3 per cent of the revenue expected in 2018, this figure is still small, suggesting an issue of tax evasion and ineffective tax policy. Using the Viet Nam Household Living Standard Surveys 2010, 2012, 2014, and 2016 and the expenditure-based approach pioneered by Pissarides and Weber, this paper first applies the non-linear least squares method to distinguish under-declaration rates for various income sources, and then uses a static microsimulation SOUTHMOD model to estimate the impact of income under-reporting on the scale of tax evasion and income inequality of Viet Nam. The paper finds that the officially reported income only accounts for 80 per cent of the true income, leaving 20 per cent unreported. Consequently, without income under-reporting, tax revenue in Viet Nam would increase by about VND23,000 billion (equivalent to US1.03 billion) and the Gini coefficient for disposable income would increase from 0.379 to 0.409.
Keywords: D12; H24; H25; H26; 330; Engel curve; income inequality; income under-reporting; permanent income; tax evasion; Viet Nam